2012
DOI: 10.1136/ejhpharm-2012-000074.203
|View full text |Cite
|
Sign up to set email alerts
|

An alternative treatment for Candida infections with Nigella sativa extracts

Abstract: Background Nigella sativa is a herb from the Mediterranean region with antidiabetic, bronchodilator, antioxidant, hepatoprotective, lipid lowering, anti-inflammatory and analgesic properties. Purpose This study aimed to reveal the antifungal activity of aqueous, methanolic and chloroform extracts obtained from the plant seeds, compared with the effect of traditional antifungals. Materials and methods Using standard mycological diagnostic methodology The authors isolated and identified 20 strains of Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…A 5-fold decrease in Candida in kidneys, 8-fold in liver and 11-fold in spleen was observed in the groups of animals post-treated with the plant extract. These findings were also confirmed by Histopathological examination of the respective organs [30] . Antidermatophyte activity of ether extract of N. sativa and TQ was tested against eight species of dermatophytes: four species of Trichophyton rubrum and one each of Trichophyton interdigitale, Trichophyton mentagrophytes, Epidermophyton floccosum and Microsporum canis using Agar diffusion method with serial dilutions of ether extract of N. sativa, TQ and griseofulvin.…”
Section: Antifungal Activitysupporting
confidence: 61%
See 4 more Smart Citations
“…A 5-fold decrease in Candida in kidneys, 8-fold in liver and 11-fold in spleen was observed in the groups of animals post-treated with the plant extract. These findings were also confirmed by Histopathological examination of the respective organs [30] . Antidermatophyte activity of ether extract of N. sativa and TQ was tested against eight species of dermatophytes: four species of Trichophyton rubrum and one each of Trichophyton interdigitale, Trichophyton mentagrophytes, Epidermophyton floccosum and Microsporum canis using Agar diffusion method with serial dilutions of ether extract of N. sativa, TQ and griseofulvin.…”
Section: Antifungal Activitysupporting
confidence: 61%
“…Thus, it was concluded that TQ may have potential implication in breast cancer prevention and treatment and anti-tumor effect of TQ may also be mediated through modulation of the PPAR-γ activation pathway [59] . It was also revealed in a study of the assessment of the chemo-preventive potential of crude oils in N. sativa on tumor formation using a well-established rat multi-organ carcinogenesis model featuring initial treatment with five different carcinogens that post-initiation administration of 1 000 or 4 000 mg/L N. sativa volatile oil in the diet of male Wister rats for 30 weeks significantly reduced malignant and benign colon tumor sizes, incidences and multiplicities. The treatment also significantly decreased the incidences and multiplicities of tumors in the lungs and in different parts of the alimentary canal, particularly the esophagus and fore stomach.…”
Section: Anticancer Activitymentioning
confidence: 95%
See 3 more Smart Citations